Cost-Effectiveness of MRI-Based Identification of Presymptomatic Autism in a High-Risk Population - Williamson, Ian O.; Elison, Jed T.; Wolff, Jason J.; Runge, Carlisle Ford (Frontiers in Psychiatry, 2020)
Biological siblings of children with autism spectrum disorder (ASD) have increased risk of receiving an ASD diagnosis. In the U.S. most children with ASD are diagnosed after the optimal age to initiate early intervention which can reduce symptom severity and improve outcomes. Recent evidence suggests magnetic resonance imaging (MRI) in the first year of life can predict later diagnostic status in high-risk siblings. We investigated whether MRI-based screening is a cost-effective method for assigning early intervention. A hybrid decision tree/Markov model was used to evaluate two MRI-based screening strategies, at 6 and 12 months of age. Primary outcomes were costs in U.S. dollars and quality-adjusted-life-years (QALYs). Results were reported as incremental cost-effectiveness ratios (ICERs). Costs were estimated from societal, healthcare, and educational perspectives. One-way and probabilistic sensitivity analyses were performed. From a societal perspective, the ICER for MRI-based screening at six months was $49,000 per QALY when compared to the status quo, implying that such screening is cost-effective at willingness-to-pay (WTP) thresholds of $50,000-$100,000 per QALY. From the health care and educational perspectives, the ICERs were larger at $99,000 and $76,000 per QALY respectively. Sensitivity analysis identified that the parameters most influential in affecting cost-effectiveness were the prevalence of ASD and/or co-occurring intellectual disability. MRI specificity also has significant impacts which add to the uncertainty of the results. Future work is needed to determine the sensitivity and, in particular, the specificity of MRI with more certainty. Notably, the cost of the MRI-based screening had the least impact.